2013
DOI: 10.1177/0307174x1304000503
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Climatic Factors and Mechanical Loading on the Properties of Carbon-Fibre-Reinforced Plastic Based on An Epoxy Binder

Abstract: For carbon-fibre-reinforced plastic based on epoxy binder EDT-69N, an investigation was made of the effect of climatic factors in accelerated heat and humidity tests and in natural climatic tests under static and cyclic loading on change in the residual strength of the material in bend, its moisture content, and structural transformations in the material (glass transition region and glass transition temperature).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…One of the main manifestations of the impact of environmental factors on PCM is the saturation of their structure with moisture [20][21][22]. In this case, the capillary effect of moisture penetration through cracks and pores in the structure of the matrix and the IFL is important, which leads to the wedging of the structure when moving along the capillary (Rebinder effect).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main manifestations of the impact of environmental factors on PCM is the saturation of their structure with moisture [20][21][22]. In this case, the capillary effect of moisture penetration through cracks and pores in the structure of the matrix and the IFL is important, which leads to the wedging of the structure when moving along the capillary (Rebinder effect).…”
Section: Resultsmentioning
confidence: 99%
“…According to research materials [20][21][22], aging processes and moisture accumulating in the porous structure, diffusing into the matrix and adsorbing on the surface of the fibers in the interfacial layer (IFS) have the greatest effect on the strength and rigidity of PCM products. At the same time, there is practically no information about the effect of pretreatment of cured PCMs in a UHF electromagnetic field on the change in their rigidity after exposure in natural environmental conditions.…”
Section: Problem Statementmentioning
confidence: 99%
“…One of the main manifestations of the impact of environmental factors on PCM is the saturation of their structure with moisture [20][21][22]. Of great importance is the capillary effect of moisture penetration through cracks and pores, which leads to wedging of the structure as it moves through the capillary (Rebinder effect).…”
Section: Resultsmentioning
confidence: 99%
“…During the research carried out in 2015-2020 the author experimentally established an increase in the strength properties of cured carbon fiber and fiberglass after impact on them within 1-2 minutes by a UHF of tne electromagnetic field with a frequency of 2450: limiting shear stresses by an average of 40%, three-point bending -by (7-13)%, interlayer move -by (14-16)% [16][17][18][19]. However, the issue of maintaining the achieved effects under the influence of the time factor and under the conditions of external climatic influences of the environment remains unclear, which is important because, according to the research materials [20][21][22], it is the aging processes and moisture that exert the greatest influence on the performance of PCM products accumulating in a porous structure, diffusing into the matrix and adsorbing on the fiber surface in the interfacial layer (IFL). At the same time, the external environment has the most negative effect on structural elements made of fiberglass due to its increased hydrophilicity in comparison with carbon fiber…”
Section: Problem Statementmentioning
confidence: 99%
“…The works [7,8] devoted to PCM on the basis of epoxy binders were studying the influence of climatic factors through accelerated hygrothermal and natural climatic tests at static and cyclic loads on the change of residual strength of a material via bending, moisture content and structural transformations in the glass transition range of a material. It is revealed that the static load increases the moisture content, reduces the bending strength and glass transition temperature, as well as the glasstransition range.…”
Section: Introductionmentioning
confidence: 99%